Knowledge Management System Pada PT. Central Bearing Sentosa Pekanbaru - Diansyah, Risnal; Arribe, Edo (SATIN - Sains dan Teknologi Informasi, 2018)
Utilization of information technology can answer to the challenge of using knowledge management into the Knowledge Management System (KMS) application. One method that can be used to build KMS is Zack & Meyer Model combined with Nonaka & Takeuchi Model. The stages of the Zack & Meyer model are Acquire, Refine, Store, Distributed, and Present. As for the Nonaka & Takeuchi Model consist of Socialization, Externalization, Combination, and Internalization. PT. Central Bearing Sentosa (CBS) is a company that has many branches and one of them is in the city of Pekanbaru. The high flow of employee going in and out into the company makes PT. CBS requires strategies to help new employees adaptation process. In this case, the steps in the Zack & Meyer model are applied to PT. CBS. The goal is to get the application features relevant to the existing state in PT. CBS. Based on research conducted, the results obtained shows that the KMS built on PT. CBS has a set of features that consist of discussion forums, knowledge sharing, online meetings, messaging, libraries, wikis, and marketing maps